CD5 ablation enhances persistence and antitumor potency of engineered T cells by mitigating exhaustion and promoting cytotoxicity - Wu, Jia; Cheng, Jiali; Zhu, Li; Gao, Qiang; Lin, Haolong; Zeng, Yuhao; Li, Yong; Li, Weini; An, Ning; Huang, Liang; Xiao, Min; Li, Dengju; et al. (Journal for immunotherapy of cancer, 2025)
BackgroundWhile chimeric antigen receptor (CAR)-T cell therapy has transformed the treatment landscape for certain hematologic malignancies, therapeutic resistance and disease relapse highlight the critical need to improve the durability of clinical responses. The limited in vivo persistence and antitumor efficacy of CAR-T cells remain major barriers to achieving sustained therapeutic outcomes. Although CD5 has been extensively studied as a therapeutic target in cancers, particularly T-cell malignancies, its role as an immunomodulatory molecule in T cell-based immunotherapy remains poorly understood. Here, we developed a CD5-deficient T cell-based immunotherapy using the CRISPR-Cas9 system to address these limitations and enhance antitumor potency.MethodsEmploying green fluorescent protein knock-in murine models alongside clinical specimens, we examined the in vivo persistence of CD5-deficient T cells and their influence on T-cell receptor (TCR) clonality diversity. The antitumor efficacy of CD5-deficient engineered T cells was assessed in tumor cell line-derived xenograft murine models. To elucidate underlying mechanisms, we performed a comprehensive evaluation of the activation, expansion and infiltration of CD5-deficient engineered T cells in response to antigen stimulation, as well as their exhaustion dynamics under conditions of repeated antigen exposure.ResultsOur study identifies CD5 as a bona fide inhibitory immunomodulatory molecule. CD5 ablation significantly enhances T cell functionality by enhancing the activation level, mitigating exhaustion, promoting CD8+ T cell expansion, and improving in vivo persistence. Single-cell transcriptomic profiling of patient-derived CD5-deficient T cells revealed distinct effector subsets with elevated cytotoxicity markers and cell cycle regulators, such as STMN1, which correlate with enhanced expansion while preserving clonal diversity, as evidenced by TCR repertoire analysis.ConclusionsThese collective findings establish CD5 ablation as a viable strategy to circumvent the intrinsic limitations of current T cell-based therapies, providing a mechanistic rationale for clinical translation.